The contribution of ICT to the education of students with special educational needs in the period of Covid-19 - Geralexis, Ioannis; Karabatzaki, Zoe; Riga, Anna (Eximia, 2023)
Through this quantitative educational approach, there is an attempt to investigate the views and attitudes of secondary teachers in relation to the use of ICT in the teaching of students with special educational needs and to highlight their contribution during distance learning due to covid 19. The present dissertation constitutes quantitative research in the field of special education with a view to yielding valuable conclusions. The results showed that the teachers hold positive views and attitudes towards the use of ICT for the teaching of students with special needs. It appears that age, years of service and education level constitute factors of differentiation in teachers’ views. A positive differentiation was observed in the performance of students with special educational needs due to the use of ICT. The totality of teachers express the need for ICT training, readjustment of curriculums, whereas the preservation of the use of ICT in the post-covid era is statistically significant. The results of the study are discussed in terms of educational placement.